ANIMO ORANG TUA MENYEKOLAHKAN ANAKNYA KE SEKOLAH MENENGAH PERTAMA TAHFIZH QUR’AN (SMP TQ) AN- NAJIYA NAGARI KOTO BARU. KEC. LUHAK NAN DUO KAB. PASAMAN BARAT - Nuzuli Fitriana; Junaidi; Salmi Wati; Wedra Aprison (KOLONI, 2022)
The background of this research is related to the people of Nagari Koto who do not want to send their children to SMP Tahfidzul Qur'an An-Najiya. This will be explored/searched for information about what causes parents in Nagari Koto Baru not to want to send their children to An-Najiya Middle School. This study uses a descriptive qualitative approach, using key informants from parents and students. And the supporting informant in this study was the Principal of SMP TQ An-Najiya Pasaman Barat. In data collection, data collection techniques used are interviews. The data analysis techniques used are data reduction, data presentation and drawing conclusions. To test the data using source triangulation, which is to compare the results of interviews conducted on key informants, supporting informants and the results of direct observations by the author. The results showed that the people of Nagari Koto Baru did not want to send their children to SMP Tahfiz Qur'an (TQ) An-Najiya Nagari Koto Baru. district. Luhak Nan Duo Kab. This is due to the lack of parental fees. The cause of the low public interest in sending their children to SMPTQ An-Najiya is due to the lack of parental fees, school status, location and educational facilities that make people not want to send their children to SMPTQ An-Najiya.  Keywords: Parents' enthusiasm, sending their children to Tahfiz Qur'an Middle School